Debating Medical Utility, Not Futility: Ethical Dilemmas in Treating Critically Ill People Who Use Injection Drugs. Issue 2 (June 2018) - Baldassarri, Stephen R.; Lee, Ike; Latham, Stephen R.; D'Onofrio, Gail
Physicians who care for critically ill people with opioid use disorder frequently face medical, legal, and ethical questions related to the provision of life-saving medical care. We examine a complex medical case that illustrates these challenges in a person with relapsing injection drug use. We focus on a specific question: Is futility an appropriate and useful standard by which to determine provision of life-saving care to such individuals? If so, how should such determinations be made? If not, what alternative decisionmaking framework exists? We determine that although futility has been historically utilized as a justification for withholding care in certain settings, it is not a useful standard to apply in cases involving people who use injection drugs for non-medical purposes. Instead, we are welladvised to explore each patient's situation in a holistic approach that includes the patient, family members, and care providers in the decision-making process. The scope of the problem illustrated demonstrates the urgent need to definitively improve outcomes in people who use injection drugs. Increasing access to high quality medication-assisted treatment and psychiatric care for individuals with opioid use disorder will help our patients achieve a sustained remission and allow us to reach this goal.